The Formation of Sunni and Shia Theology in Early Islam: A Collective Memory Perspective on Power and Identity - Masugi, Ibrahim Achmad Farrel Mahardika; Wiwik Setiyani (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigates how traumatic experience and power dynamics after the Prophet Muhammad’s death shaped the theological and collective-psychological divergence of Sunni and Shia Islam. The core question concerns how the First Fitnah and the Karbala tragedy functioned not merely as political conflicts but as catalysts of enduring psychological patterns that inform doctrine and ritual. Grounded in the theory of collective memory developed by Maurice Halbwachs, this study employs a qualitative library research approach to examine classical texts, historical records, and modern scholarship. It argues that historical events are not passively remembered but actively reconstructed within social frameworks, enabling their transformation into enduring theological meanings. Findings reveal that the Shia community transformed the trauma of betrayal and martyrdom into a theology of resistance rooted in the Imamate, the memory of Karbala, and the concept of occultation, fostering defensive solidarity and an identity structured around suffering. In contrast, Sunnism developed a theology of legitimacy and social harmony through the caliphate, cultivating obedience and a psychological drive for stability to counter fears of fragmentation. The results affirm that both theological traditions are products of the dynamic interplay between power, history, and collective memory mechanisms that shape and transmit religious identity across generations. [Penelitian ini mengkaji bagaimana pengalaman traumatis dan dinamika kekuasaan pasca wafat Nabi Muhammad SAW membentuk divergensi teologis dan psikologi kolektif antara Sunni dan Syiah. Permasalahan utama penelitian ini adalah bagaimana Fitnah Kubro dan tragedi Karbala tidak hanya berfungsi sebagai konflik politik, tetapi juga sebagai katalis bagi terbentuknya pola psikologis yang bertahan lama dan memengaruhi doktrin serta praktik keagamaan. Berlandaskan teori memori kolektif yang dikembangkan oleh Maurice Halbwachs, penelitian ini menggunakan pendekatan kualitatif berbasis studi kepustakaan dengan menelaah teks klasik, catatan sejarah, dan literatur akademik kontemporer. Penelitian ini berargumen bahwa peristiwa historis tidak diingat secara pasif, melainkan direkonstruksi secara aktif dalam kerangka sosial tertentu sehingga menghasilkan makna teologis yang berkelanjutan. Hasil penelitian menunjukkan bahwa komunitas Syiah mentransformasikan trauma pengkhianatan dan kesyahidan menjadi teologi resistensi yang berakar pada konsep Imamah, memori Karbala, dan doktrin ghaib, yang menumbuhkan solidaritas defensif serta identitas berbasis penderitaan. Sebaliknya, Sunni mengembangkan teologi legitimasi dan harmoni sosial melalui konsep khilafah, yang menumbuhkan etos kepatuhan serta dorongan psikologis untuk menjaga stabilitas guna meredam ketakutan terhadap disintegrasi. Temuan ini menegaskan bahwa kedua tradisi teologis merupakan hasil dari interaksi dinamis antara kekuasaan, sejarah, dan mekanisme memori kolektif yang membentuk serta mentransmisikan identitas keagamaan lintas generasi.]